An arena for higher powers : ceremonial buildings and religious strategies for rulership in late Iron Age Scandinavia - Sundqvist, Olof. (Numen Book Series, 2015)
In An Arena for Higher Powers Olof Sundqvist investigates ceremonial buildings and religious ruler strategies in Late Iron Age Scandinavia (i.e. AD 550-1050/1100). The author offers here an account of the role played by religion in political undertakings among the pre-Christian ruling elites at halls and cultic buildings. Sundqvist applies a regional approach, so as to be able to account for the specific historical, cultural and social contexts. The focus is mainly on three regions, the Lake Mälaren area in Sweden, Trøndelag in Norway, and Iceland. Since the political structure and other contextual aspects partly differed in the three regions, the religious strategies for gaining legitimacy and authorization at the sanctuaries also varied to some extent in these areas.